2018
DOI: 10.1136/neurintsurg-2018-014542
|View full text |Cite
|
Sign up to set email alerts
|

Beam hardening artifacts of liquid embolic agents: comparison between Squid and Onyx

Abstract: BackgroundInitial clinical experience with Squid shows subjectively reduced artifacts on post-embolization CT scans compared with Onyx. To further investigate these observations, we aimed to perform a comparison of artifacts between Squid and Onyx in a controlled in vitro model.Materials and methodsOnyx 18 and all four variants of Squid (Squid 18, Squid 18 low density (LD), Squid 12, Squid 12 LD) were each injected in dimethylsulfoxide (DMSO) compatible test tubes. The tubes containing precipitated embolic mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 16 publications
1
37
0
Order By: Relevance
“…This feature may be the result of the smaller amount of tantalum inside SQUID compared to Onyx (30% less than Onyx). 8 In our cases, SQUID 12 demonstrated faster penetration toward the fistula, ease of plug formation and no entrapment of the microcatheter. We achieved cDAVF cure on immediate post-treatment angiography in 17 out of 19 patients with a complete occlusion rate of 89%.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…This feature may be the result of the smaller amount of tantalum inside SQUID compared to Onyx (30% less than Onyx). 8 In our cases, SQUID 12 demonstrated faster penetration toward the fistula, ease of plug formation and no entrapment of the microcatheter. We achieved cDAVF cure on immediate post-treatment angiography in 17 out of 19 patients with a complete occlusion rate of 89%.…”
Section: Discussionsupporting
confidence: 48%
“…11 Compared to Onyx, it seems to have a restrained reflux and fewer artifacts on CT. 12 SQUID is an EVOH copolymer that has become recently available in 4 different formulations, of which the most innovative is SQUID 12 because of its lower viscosity. 8 Currently, PHIL 25% LV is the only commercially available version of nonadhesive LEAs comparable to SQUID 12. 13 About this, Vollherbst et al reported not significantly differences between these 2 embolic agents in an in vivo endovascular embolization model, in particular in terms of embolization extent and the amount of reflux.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Squid-18, such as in case of Onyx use, is suggested for initial plug formation, while the new formulation Squid-12 can improve vascular penetration and spread more distally. Another advantage of Squid over Onyx is related to the reduced percentage (30%) of tantalum which can improve vessels visualization during embolization and limit metallic artifacts at imaging follow-up (Gioppo et al, 2017), as also recently demonstrated (Pop et al, 2018). Squid was always administered using DMSO-compatible coaxial microcatheters as straight Renegade Hi-flo (Boston) or curved Carnelian (Tokai): the peculiar cobra-shaped tip of Carnelian was useful in selected cases of marked tortuosity of the target artery, as for example in VAA (splenic) or type 2 endoleak embolization.…”
Section: Discussionmentioning
confidence: 79%
“…They are similar but Squid, marketed more recently, is also available in the less viscous formulation which spreads more distally and may be useful in selected cases, as for example to treat arteriovenous malformations [8,14]. Another advantage of Squid over Onyx is the reduced percentage (less 30%) and smaller size of tantalum particles conditioning fewer metallic artefacts on CT images [15,16]. Compared to adhesive liquid embolic agents as glue, Squid and Onyx are more expensive but can provide a more predictable formulation-dependent distribution, resulting in more homogeneous casts.…”
Section: Discussionmentioning
confidence: 99%